PENGEMBANGAN E-LABORATORY INSTRUCTION MODEL GUIDED INQUIRY BERBASIS BLENDED LEARNING PADA MATERI TITRASI ASAM BASA (Jurnal Inovasi Pendidikan Kimia, 2021)
Learning practicum material has not been carried out optimally. This is because students do not understand how to use practical tools and processes, so students' skills in implementing them are still not good. Blended learning is a way to minimize these problems. This study aims to see the feasibility, effectiveness and practicality of the e-laboratory guided inquiry learning model based on Blended Learning on acid-base titration material. Model development is carried out using the 4D model. This research through the 3D stage is by defining (Define), Design (Design) and Development (Develop). Data collection techniques through interviews, documentation, questionnairs and observation. The result shows that the validation of media experts obtained an average score of two validators of 75.5 and the results of the validation of material experts obtained an average score of two validators of 53 which means that the e-laboratory instruction is very feasible to use. The results of observations of student skills during large-scale trials showed that overall e-laboratory instruction was declared "Very Effective" with a percentage of 88.3%. Based on the results of the questionnaire responses of students showed that e-laboratory instruction stated "Practical" was used with a percentage of 82.4%.